The Regional Western Sweden SOM Survey 1995 - SOM Institute, University of Gothenburg (University of Gothenburg, 1997)
This is the fourth study in the series of SOM-surveys carried out in Western Sweden exclusively. The questionnaire was divided into six subject fields: mass media; politics and society; the municipality of Göteborg; traffic and environment; leisure and housing; and background. Most of the questions are replications of questions asked in one or several previous SOM-surveys. New questions in the 1995 survey dealt with: reason giving up morning paper subscription; confidence in the way work is done by a number of occupational groups; opinion on the local administration and people employed by the local authorities; regional cooperation in western Sweden; the importance of being engaged in issues regarding different levels of society, i.e. EU, Sweden, western Sweden, the Göteborg region, the municipality, etc.; the financing of public transport; opinion on propositions concerning the environment; road safety; local advertisement papers and other local papers containing news and offered free of charge; time devoted to radio, daily papers and television; the importance of different subject fields in evening papers; major weekly shopping; view of the Bible; and opinion on major events arranged in Göteborg the last year. The respondent was also asked about the participation in the first Swedish election to the EU-parliament in the fall of 1995, kind of ballot used, and if the possibility to vote on a specific person was used.

Purpose:

Study attitudes and behaviours that are linked to local and regional issues and phenomena

Detta är den fjärdje studien i serien SOM-undersökningar genomförda i Västsverige. Undersökningens frågeformulär var indelat i sex områden: massmedia; politik och samhälle; Göteborgs kommun; trafik och miljö; fritid och boende; samt bakgrundsfrågor. Huvuddelen av enkätens frågor återfinns även i en eller flera av de tidigare undersökningarna. Nya frågeställningar i 1995 års undersökning tar upp: anledningar till att upphöra med en tidningsprenumeration; förtroende för det sätt på vilket ett antal yrkesgrupper sköter sitt arbete; inställning till den kommunala förvaltningen och de anställda i hemkommunen; inställning till det regionala samarbetet i Västsverige; betydelsen av att engagera sig i frågor på olika nivå i samhället, dvs EU-frågor, rikspolitiska, västsvenska, regionala och kommunala frågor samt frågor på stadsdelsnivå; finansieringen av kollektivtrafiken; inställning till ett antal förslag beträffande miljön i hemkommunen; trafiksäkerhet; läsning av lokala annonsblad eller lokal gratistidning som innehåller nyheter; tid ägnad åt massmedia; olika tidningsinnehålls betydelse; större veckoinköp; uppfattning om Bibeln; samt inställning till stora arrangemang som ägt rum i Göteborg senaste året. Respondenterna tillfrågades även om deltagandet i det första svenska valet till EU-parlamentet hösten 1995, vilken typ av valsedel man använt, samt om man använt sig av möjligheten att personrösta.

Syfte:

Studera attityder och beteenden som är knutna till lokala och regionala frågor och företeelser
Den västsvenska SOM-undersökningen 1995
Väst-SOM 1995
Keywords: internal politics; inrikespolitik; CORS; CORS; Media; Media; Environment and conservation; Miljö och naturvård; Political behaviour and attitudes; Politiska beteenden och attityder; Leisure, tourism and sport; Fritid, turism och sport; TRANSPORT AND TRAVEL; TRANSPORT OCH RESOR; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap; Media and Communication Studies; Medie- och kommunikationsvetenskap